Riflessioni su alcune terrecotte rinvenute in territorio ostiense e portuense - D’Alessio, Alessandro; Genovese, Cristina; Martelli, Elena (O T I V M, 2024)
The finds from the Roman-Ostian area, distributed in numerous museum collections, were recovered under various circumstances: from looting during the second half of the 19th century to digs with no stratigraphic method and limited data recording in the first half of the 20th century, up to more rigorous and multidisciplinary investigations from the second half of the 20th century onwards. Terracottas are present in considerable numbers ranging from architectural types, some evidence of the earliest phases of the colony, to reliefs representing scenes of people at work, to the so called “forme fittili ostiensi” i.e. moulds formed by two interlocking halves and decorated on the interior with scenes from the amphitheatre, theatre and circus. This article focuses on two case studies, applying the Italian iconographical tradition in combination with North-European approaches towards context, finds distribution and social identity, and using experimental archaeology. The first case study concerns a group of terracotta figurines representing porters (saccarii). The analyses of contextual data together with the porters’ social identity have contributed to hypothesize their local production and their possible cultual meaning connected to celebrations, linked to professional associations and the Antonine-Severan dynasties. The second group consists of wheel-made clay pigs, characterized by ovoid-shaped bodies embellished with floral decoration and glass insets. With the aid of experiments and detailed contextual examination, it has been highlighted how the objects in question bore multiple meaning during its life-cycle: from one-use drinking vessel to toy, to protector or replacement of a sacrifice for a deity in children funerary contexts. The representation of pigs and ears of wheat as attributes in terracottas, such a genius cucullatus from Ostia, are possibly a gesture of pietas for a mors immatura, linked to Telesphorus/underworld deities. The two case studies exemplify the multiplicity and complexity of interpretative readings that underlie terracottas, rendering the cultural, artistic and commercial peculiarities of the Ostia-Portus system even more perspicuous.